Continuum Generation by Generation: The representation of Chinese traditions at the China Pavilion of the 57th Venice Biennale. (1st September 2019) - De Nigris, Ornella
AbstractThis article focuses on the China pavilion of the 57th Venice Biennale as a case study. The theme of the pavilion, Continuum ‐ Generation by Generation, revolved around the long history of Chinese tradition and offered a visual re-elaboration of it by means of contemporary art and folk art. The works exhibited drew on Chinese mythology, masterpieces of Chinese art history, philosophical concepts and handcraft traditions, hence presenting a variegated image of (contemporary) Chinese art. This exhibition offers opportunities for a critical reading of the relationship between contemporary art and tradition implied by the theme Continuum, and I will explore the narrative and curatorial discourse it presented to the audience.